Simulasi Monte Carlo dalam Memprediksi Tingkat Pendapatan Penjualan Kuliner - Muhammad Ihksan; Yuhandri Yunus (Jurnal Informatika Ekonomi Bisnis, 2021)
Radja Minas is one of the culinary places located in the city of Padang with more than 30 employees. With the development of Radja Minas, of course, a good management strategy is needed. One way to do a revenue simulation, sales revenue simulation is a process of drawing or predicting sales. This study aims to predict the average sales revenue, so that it becomes a recommendation for use in making management strategies. The data processed in this research is sales data from 2017 to 2019 which comes from Radja Minas. This data will be processed using the monte Carlo method. The results of the tests that have been done have an accuracy rate of 92.66%. The high level of accuracy from the results of predictive data processing, this research is very precise and suitable for optimizing sales revenue. So that this research becomes a recommendation to be used in making a management strategy at Radja Minas in the future.